Anorectal conditions associated with human papillomavirus. Cienfuegos, 2020-2021 - Yuselis María Sánchez Reyes; Jorge Luis Estepa Pérez; José Antonio Feliú Rosa; Jorge Luis Estepa Ramos; Lianet González Gutiérrez (Medisur)
Foundation: the human papillomavirus is a double-stranded DNA virus that infects the squamous epithelium in healthy individuals to produce warts and condylomas; it constitutes a health problem that affects globally. Objective: to identify the prevalence of anorectal conditions associated with human papillomavirus. Methods: descriptive research that included all patients with anorectal conditions associated with the human papillomavirus, from November 1st, 2020 to December 31st, 2021, treated in the Coloproctology Service of the Gustavo Aldereguía Lima Hospital, in Cienfuegos. The information was obtained from the clinical record and a data collection model. The analyzed variables were: age, sex, risk factors, clinical and pathological characteristics, topographic location of the lesion, and surgical technique applied. Results: the male sex and the age group between 30 and 39 years predominated; Cienfuegos was the most affected municipality. Relationships with multiple partners and early intercourse were the most significant risk factors; the anal canal was the most frequent location and ulcerectomy was the most used technique; Complications included delayed healing and urinary retention; most progressed satisfactorily after three months. Conclusions: human papillomavirus infection is related to the appearance of anal conditions.